Comparison of Molecular Adsorbents Recirculating System (MARS) dialysis with combined plasma exchange and haemodialysis in children with acute liver failure - Schäfer, Betti; Schaefer, Franz; Engelmann, Guido; Meyburg, Jochen; Heckert, Karl Heinz; Zorn, Markus; Schmitt, Claus P. (Nephrology, dialysis, transplantation, 2011)
Background. Molecular Adsorbents Recirculating System (MARS) is an extracorporeal liver support system eliminating albumin-bound and water-soluble substances. While it is increasingly applied in patients with acute liver failure (ALF), no comparison with standard dialysis methods has yet been performed. Methods. This is an analysis of ten children (0.1-18 years) with ALF, who underwent a total of 22 MARS sessions. Standard adult MARS sets were used in seven (23.5-72 kg) and MARS Mini in three children (2.8-13 kg). In eight children, MARS was alternated with combined plasma exchange (PE) and haemodialysis (HD) treatments. Mean treatment duration was 7.2 (6-10) h for MARS and 5.7 (4.5-6.6) h for PE/HD. Results. Standard MARS treatment only slightly decreased serum bilirubin (16.3 ± 6.5-13.8 ± 5.9 mg/dL) and ammonia (113 ± 62-99 ± 68 μmol/L) and international normalized ratio (INR) tended to increase (1.5 ± 0.3 and 2 ± 1.1). Mini-MARS did not reduce serum bilirubin (19.7 ± 3-20.5 ± 3.2 mg/dL), ammonia slightly decreased (70 ± 24-56 ± 9 μmol/L) and INR increased (2.5 ± 0.7-2.9 ± 1.1, all P = n.s.). In contrast, PE/HD reduced serum bilirubin (23 ± 8.4-14.7 ± 7 mg/dL), ammonia (120 ± 60-70 ± 40 μmol/L) and INR (2.4 ± 0.8-1.4 ± 0.1, all P < 0.05). Intraindividual comparison showed a slight increase in bilirubin by 2 ± 22% with MARS and a reduction by 37 ± 11% with PE/HD (P < 0.001 versus MARS) and a decrease in ammonia of 18 ± 27 and 39 ± 23% (P < 0.05). INR increased during MARS by 26 ± 41% and decreased with PE/HD by 37 ± 20% (P < 0.01). All treatment sessions were well tolerated. Five children died, including the three children treated with Mini-MARS. Conclusion. Our experience suggests superior efficacy of combined PE/HD as compared to intermittent MARS therapy for treating ALF.